Nociceptin receptor activation does not alter acquisition, expression, extinction and reinstatement of conditioned cocaine preference in mice - Sartor, GC (Brain Res, 2015)
Growing evidence indicates that targeting nociceptin receptor (NOP) signaling may have therapeutic efficacy in treating alcohol and opioid addiction. However, little is known about the therapeutic value of selective NOP agonists for the treatment of cocaine dependence. Recently, we identified a highly selective, brain-penetrant NOP small molecule agonist (SR-8993), and using this compound, we previously showed that nociceptin receptor activation attenuated consolidation of fear-related memories. Here, we sought to determine whether SR-8993 also affects the rewarding properties of cocaine. Using a conditioned place preference (CPP) procedure, we show that SR-8993 (3 or 10 mg/kg) failed to disrupt acquisition or expression of cocaine CPP (7.5 or 15 mg/kg) in C57BL/6 mice. Additionally, SR-8993 did not affect rate of extinction or reinstatement (yohimbine- and cocaine-induced) of cocaine CPP. These studies indicate that selective activation of NOP may not be sufficient in reducing behavioral responses to cocaine.